Performance comparison of complementary and AND subtraction detection techniques for hybrid SCM SAC-OCDMA system - Sahbudin, Ratna Kalos Zakiah; Syed Junid, Syed Alwee Aljunid; Abdullah, Mohamad Khazani; Othman, Mohamed; Samad, M. D. A.; Mahdi, Mohd Adzir; Ismail, Mahamod (IEEE, 2006)
The subtraction detection techniques for a hybrid SCM spectral-amplitude-coding (SAC) OCDMA using double weight (DW) code family are investigated. The experimental simulation results show that the proposed new subtraction detection technique provides a better system performance.